Lama Menjalani Hemodialisa Berhubungan Dengan Kecemasan Pada Pasien Gagal Ginjal Kronik - Lilipory, Mevi (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2023)
Chronic Kidney Failure is a progressive and irreversible decline in kidney function. Hemodialysis is one of the therapies performed on chronic kidney failure sufferers. This study aims to determine the relationship between the length of time undergoing hemodialysis and the anxiety of Chronic Kidney Failure patients at Hospital X. The type of research used is analytical with a cross sectional approach. The sampling technique was accidental sampling with a total of 43 respondents using the Chi Square statistical test. The results of the research show that there is a significant relationship between the length of undergoing hemodialysis and anxiety in Chronic Kidney Failure patients at Hospital.Keywords: Chronic Renal Failure; Anxiety; Long time undergoing hemodialysis